Characterization and role of collagen gene expressing hepatic cells following partial hepatectomy in mice. Issue 2 (17th February 2023) - Kimura, Yusuke; Koyama, Yukinori; Taura, Kojiro; Kudoh, Aoi; Echizen, Kanae; Nakamura, Daichi; Li, Xuefeng; Nam, Nguyen Hai; Uemoto, Yusuke; Nishio, Takahiro; Yamamoto, Gen; Seo, Satoru; et al.
Abstract : Background and Aims: The mechanism underlying liver regeneration following partial hepatectomy (PH) is not fully elucidated. We aimed to characterize collagen gene expressing hepatic cells following PH and examine their contribution to liver regeneration. Approach and Results: Col‐GFP mice, which express GFP under the control of the collagen gene promoter, were used to detect collagen gene expressing cells following PH. The GFP‐expressing cells were analyzed via single‐cell RNA sequencing (scRNA‐seq). Additionally, Col‐ER Cre/RFP and Col‐ER Cre/DTA mice were utilized to examine the cell fates and functional roles of collagen gene expressing cells in liver regeneration, respectively. The number of collagen gene expressing cells was found to be increased on day 3 and subsequently decreased on day 7 following PH. ScRNA‐seq analysis of sorted collagen gene expressing cells showed that the regenerating liver was characterized by three distinct hepatic stellate cell (HSC) clusters, including one representing classic myofibroblasts. The other HSC clusters included an intermediately activated HSC cluster and a proliferating HSC cluster. Of these, the latter cluster was absent in the CCl4 ‐induced liver fibrosis model. Cell fate tracing analysis using Col‐ER Cre/RFP mice demonstrated that the collagen gene expressing cells escaped death during regeneration and remained in an inactivated state in the liver. Further, depletion of these cells using Col‐ER Cre/DTA mice resulted in impaired liver regeneration. Conclusions: Heterogeneous HSC clusters, one of which was a unique proliferating cluster, were found to appear in the liver following PH. Collagen gene expressing cells, including HSCs, were found to promote liver regeneration. Abstract :